2019
DOI: 10.1080/14992027.2019.1602289
|View full text |Cite
|
Sign up to set email alerts
|

Noise exposure as a risk factor for acoustic neuroma: a systematic review and meta-analysis

Abstract: Objective: To investigate whether acoustic neuroma is associated with noise. Design: PubMed, Cochrane, Embase and CINAHL databases were searched. A meta-analysis was performed to calculate odds ratio (OR) and 95% confidence interval (CI) using quality-effect models. Study sample: A total of 8 studies with moderate or high quality involving 75,571 participants met the inclusion criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…For example, this bias is commonly observed in the vestibular schwannoma literature, in which persons will report significant exposures related to hearing (eg, occupational noise exposure) after learning that they have developed a tumor on their hearing nerve; however, prior objective, population-based studies that do not rely on surveys demonstrate no such association. [18][19][20] Considering these methodological limitations of prior research, we believe the data from the current study do not support the assertion that pregnancy increases the risk of developing otosclerosis nor does it contribute to worsening hearing loss.…”
Section: Discussioncontrasting
confidence: 88%
“…For example, this bias is commonly observed in the vestibular schwannoma literature, in which persons will report significant exposures related to hearing (eg, occupational noise exposure) after learning that they have developed a tumor on their hearing nerve; however, prior objective, population-based studies that do not rely on surveys demonstrate no such association. [18][19][20] Considering these methodological limitations of prior research, we believe the data from the current study do not support the assertion that pregnancy increases the risk of developing otosclerosis nor does it contribute to worsening hearing loss.…”
Section: Discussioncontrasting
confidence: 88%
“…In addition, systematic reviews examining associations between (occupational) noise and injuries [71•], reproductive outcomes [72,73], diabetes [77], and acoustic neuroma [75,76] were also published in the last decade.…”
Section: Other Non-auditory Health Effects Of Noisementioning
confidence: 99%
“…Two systematic reviews looked at the evidence of an association between noise exposure and acoustic neuromas. Chen et al [76] and Cao et al [75] included eight case-control studies in their meta-analyses of noise. Both studies observed high heterogeneity and inconclusive results.…”
Section: Acoustic Neuromamentioning
confidence: 99%
See 1 more Smart Citation
“…The vestibular system plays a decisive role in the spatial orientation at rest and in motion and in the formation of motor and sensory memory, which underlie all forms of sensory and motor activities. It responds to the development of disorders in the body, in particular, somatic, motor, sensory and autonomic ones with exceptionally subtle sensitivity, dynamism, objectivity of symptoms before other sensory systems, so it is of prime importance in regard to these functions (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%